Determinação de açucares em bagaço de palha de cana-de-açúcar por cromatografia líquida de alta eficiência com detecção eletroquímica utilizando eletrodos de nanotubos modificados com óxidos metálicos - Sá, Acelino Cardoso de [UNESP] (2015)
Biomass generated from the bagasse from sugarcane is a byproduct of the production process of sugar and ethanol. New applications for the bagasse have been developed among them we can highlight the production of biofuels (ethanol) of second generation. The processes for the production of second generation ethanol from biomass sugarcane involves optimizing an integrated manner in several steps: pre-treatment, hydrolysis and fermentation of the hydrolyzed products, to evaluate the efficiency of these procedures is fundamental a precise characterization of biomass sugars for conversion into ethanol, therefore it was developed the preparation and use of the glassy carbon electrode modified with carbon nanotubes containing nickel oxide-hydroxide GCE/MWCNT/NiOOH for detection and quantification of sugars in alkaline médium. It was studied electrocatalytic constant rate of sugars in GCE/MWCNT/NiOOH. These studies are important to better understand the electrodic processes involved in the GCE/MWCNT/NiOOH during the electro-oxidation of sugars to the development of analytical methods for HPLC. Analytical methods were developed using HPLC with electrodes GCE/MWCNT/NiOOH and GCE/MWCNT/CoOO for quantification of sugars in sugarcane bagasse samples. The GCE/MWCNT/NiOOH presented a detection limit 2.5×10-6 mol L-1 for arabinose, 5.4×10-6 mol L-1 for galactose, 3.4×10-6 mol L-1 for glucose and 6.6×10-6 mol L-1 for xylose. The GCE/MWCNT/CoOO showed the following detection limits: 3.4×10-6 mol L-1 for arabinose, 4.4×10-6 mol L-1 for galactose, 3.6×10-6 mol L-1 for glucose and 5.0×10-6 mol L-1 for xylose. It was observed that both electrodes exhibit similar detection limits, another feature was that in both methods were adequate in determining the sugars present in the sugarcane bagasse samples, on GCE/MWCNT/NiOOH was determined 5.9 ×10-4 mol L-1 arabinose 1.0×10-2 mol L-1 glucose and 2.8 10-3 mol L-1...